Alleviation of oxidative stress, carcass fat and plasma cholesterol in broiler chickens consuming antanan (Centella asiatica) and vitamin C - Kusnadi, Engkus (Indonesian Journal of Animal and Veterinary Sciences, 2008)
Oxidative stress (a condition where oxidant -free radical- activity dominates the antioxidant activity) in poultry may be caused by heat stress from high environmental temperature. In this research, antanan (Centella asiatica) and vitamin C was utilized as anti heat-stress agents for broilers. One hundred and twenty male broilers of 2 â 6 weeks of age were kept at 31.98 Â± 1.940C poultry house temperature during the day and 27.36 Â± 1.310C at night. The treatments consist of two kinds: two levels of vitamin C (0 and 500ppm) and three levels of antanan (0, 5 and 10% of diets). The data colected was analized for variance with a factorial in completely randomized design of 2 x 3 (2 levels of vitamin C, 3 levels of antanan) and continued with contrast-orthogonal test when applicable. The results indicated that the treatments of antanan 5% without vitamin C (A5C0), antanan 10% without vitamin C (A10C0), vitamin C 500ppm without antanan (A0C500), combination of A5 and C500 (A5C500), and combination ofÂ  A10 and C500 (A10C500) significantly (P<0.05) decreased the level of liver malonaldehida (MDA), carcass lipid and plasma cholesterol. Key Words: Oxidative Stress, Centella Asiatica, Vitamin C